2019
DOI: 10.1088/2515-7620/ab22cd
|View full text |Cite
|
Sign up to set email alerts
|

Aquaculture-induced boundary circulation and its impact on coastal frontal circulation

Abstract: With the development of coastal suspended aquaculture industry, aquaculture facilities have extended into the open sea to depths of up to 30 m. This practice will likely affect the natural ocean circulation in such areas. For a case study in the high-density aquaculture region of the coastal Yellow Sea, an aquaculture-induced boundary circulation (ABC) is identified and its effects on the background frontal circulation and cross-shore nutrient supply are examined. The ABC is composed of a southward along-bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Xuan et al. (2019) found that there is a counterclockwise cross‐boundary cell around the aquaculture boundary, with its magnitude exceeding the clockwise cross‐frontal cell generated by tidal fronts in natural conditions. The weakened onshore currents within lower layers may significantly reduce the nutrient supply for the near‐bottom water at the aquaculture boundary, which carries higher nutrient concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Xuan et al. (2019) found that there is a counterclockwise cross‐boundary cell around the aquaculture boundary, with its magnitude exceeding the clockwise cross‐frontal cell generated by tidal fronts in natural conditions. The weakened onshore currents within lower layers may significantly reduce the nutrient supply for the near‐bottom water at the aquaculture boundary, which carries higher nutrient concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study (Xuan et al, 2019) pointed out that tide-induced water convergence is the major forcing in boundary circulation. The sea surface height on the inshore side of the aquaculture boundary is much higher than that on the offshore side because of the strong friction in the aquaculture area, suggesting that water converges on the inshore side of the aquaculture boundary.…”
Section: The Role Of Suspended Aquaculture In Fontal Circulation In O...mentioning
confidence: 99%
See 1 more Smart Citation
“…The more food supplies in the water, the faster the growth. In addition, water currents play an important role in the success of culture activities in both water circulation and nutrient transport (Xuan et al, 2019).…”
Section: Journal Of Marine Studiesmentioning
confidence: 99%